2016
DOI: 10.1097/ijg.0000000000000064
|View full text |Cite
|
Sign up to set email alerts
|

Does the ISNT Rule Apply to the Retinal Nerve Fiber Layer?

Abstract: A larger number of normal eyes obeyed the IST rule compared with the ISNT rule for the RNFL thickness measured by HRT and OCT. Exclusion of the nasal sector from the analysis (IST rule) marginally improved the specificity in diagnosing glaucoma at the cost of the sensitivity, making neither of these parameters (ISNT and IST) likely to be useful clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 12 publications
2
36
2
3
Order By: Relevance
“…The percentage of eyes following the ISNT rule was 55% (44 eyes) and 36.84% (28 eyes) in the normal group and the early glaucoma group, respectively (p=0.02). Pradhan et al 15 in their study on the stratus OCT showed that the ISNT rule on RNFL was applicable to 47.1% and 23.8% eyes in their normal group and the glaucoma group, respectively. A similar study on SD-OCT showed that the ISNT rule was applicable in 42% of normal subjects 23.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The percentage of eyes following the ISNT rule was 55% (44 eyes) and 36.84% (28 eyes) in the normal group and the early glaucoma group, respectively (p=0.02). Pradhan et al 15 in their study on the stratus OCT showed that the ISNT rule on RNFL was applicable to 47.1% and 23.8% eyes in their normal group and the glaucoma group, respectively. A similar study on SD-OCT showed that the ISNT rule was applicable in 42% of normal subjects 23.…”
Section: Discussionmentioning
confidence: 98%
“…The usefulness of the NRR rules has been tested before 10–14. However, there are very few studies that look into whether the classical ISNT rule is applicable to the RNFL 15. Since the nasal rim is the last to be affected in glaucoma,16 we also tested the IST rule (inferior>superior>temporal) on the RNFL.…”
Section: Introductionmentioning
confidence: 99%
“…In normal eyes, histologic as well as intravital OCT studies have reported that RNFL is thickest in the inferior quadrant followed by the superior quadrant. 22,23 We showed that the progressive reduction in RNFL was only statistically significant in the superior quadrant, whereby there was a linear annual thinning rate of approximately 2 lm/y in DPNþve individuals. The RNFL in the inferior (the thickest) and temporal quadrants showed no statistically significant alterations over 4 years in relation to neuropathy status.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, many investigators have sought to determine whether the ISNT rule, either applied to the neuroretinal rim disc photos 1215 or to RNFL thickness measurements, 16, 17 is useful in the diagnosis of glaucoma or not. However, the optic disc photo ISNT rule studies are conflicting, with some finding the ISNT rule and its variants clinically useful, 13, 14 while others have not.…”
Section: Introductionmentioning
confidence: 99%